2011
DOI: 10.1002/ejoc.201101489
|View full text |Cite
|
Sign up to set email alerts
|

Nonenzymatic Acylative Kinetic Resolution of Racemic Amines and Related Compounds

Abstract: Acylative kinetic resolution of racemic amines occupies a highly important place among the methods for preparation of enantio enriched or pure amines. Nonenzymatic acylative kinetic resolution is usually carried out in the presence of chiral acyl‐transfer catalysts or under the action of chiral enantio‐ or diastereoselective resolving agents. Recently, this line of investigations has been rapidly developed and very interesting results of design and synthetic application of both new catalysts and chiral acylati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(28 citation statements)
references
References 172 publications
0
28
0
Order By: Relevance
“…In the presence of amine, the trans conformation is even higher in energy because the conformational changes required to avoid the strong A 1,2 strain between the hydroxamide and the ester block the approach of the amine.…”
Section: Resultsmentioning
confidence: 99%
“…In the presence of amine, the trans conformation is even higher in energy because the conformational changes required to avoid the strong A 1,2 strain between the hydroxamide and the ester block the approach of the amine.…”
Section: Resultsmentioning
confidence: 99%
“…A number of chiral N-acylating agents have been developed that proceed with excellent selectivity (s) values, with selected reagents affording amines in good ee at approximately 50% conversion. 411 For example, Ie and Fu demonstrated that 0.5 equivalent of a N-acetyl chiral planar ferrocene DMAP reagent could be used for the N-acylation of a series of arylalkylamines to afford chiral amides in up to 78% ee. Increasing the ratio of (rac)-amine to catalyst to 8:1 enabled stereoeselective amide bond formation in up to 91% ee (Figure 68 (a)).…”
Section: Redox Amidation Reactionsmentioning
confidence: 99%
“…73,[411][412][413] One strategy is to use an enantiopure stoichiometric acylating reagents that contains a stereodirecting group contained within its leaving group. This approach ideally involves selective reaction of one Figure 67 Oxidative amidation using α-bromo nitroalkanes as acyl equivalents.…”
Section: Redox Amidation Reactionsmentioning
confidence: 99%
“…It is commonly accepted that KR processes could be useful from a preparative point of view in scenarios where the s value is greater than 10 . But the situation would be problematic if the objective is to produce either of the highly enantio‐enriched products in up to quantitative yields from racemic starting materials.…”
Section: Dynamic Kinetic Resolutions In Nhc Organocatalysismentioning
confidence: 99%